Efficacy of acupuncture for lumbar disc herniation: changes in paravertebral muscle and fat infiltration – a multicenter retrospective cohort study - Yan, Liang; Zhang, Jiliang; Wang, Xianliang; Zhou, Qinming; Wen, Jingdong; Zhao, Haihong; Guo, Kai; Zeng, Jianhua (Frontiers in Endocrinology, 2024)
Objective: This study seeks to elucidate the dynamic alterations in the multifidus, erector spinae, and psoas major muscles, along with their fatty infiltration, in patients diagnosed with lumbar disc herniation treated through acupuncture. Concurrently, the Visual Analogue Scale (VAS) and Japanese Orthopedic Association (JOA) scores are employed to evaluate modifications in lumbar and leg pain and the enhancement in lumbar functionality.Methods: A retrospective multi-center cohort study enrolled 332 adult LDH patients. Participants were divided into acupuncture and rehabilitation therapy groups. The acupuncture cohort received targeted treatments at specific acupuncture points, while the rehabilitation group received traditional rehabilitative therapy. Magnetic Resonance Imaging (MRI) gauged muscle cross-sectional areas (Sm, Se, Sp) and their ratios to vertebral area (Sm/Sv, Se/Sv, Sp/Sv), and fatty infiltration areas (Sfm, Sfe, Sfp) and their ratios (Sfm/Sv, Sfe/Sv, Sfp/Sv). Pain and function were assessed using Visual Analogue Scale (VAS) and Japanese Orthopedic Association (JOA) scores pre-treatment, 2-weeks, and 3-months post-intervention.Results: A total of 332 patients were enrolled for analysis. Post-treatment, the acupuncture group exhibited increased Sm, Se, Sp and their ratios and reduced fatty infiltration areas and their ratios (P<0.05) compared to rehabilitation. Both treatments decreased VAS scores and enhanced JOA scores at both intervals (P<0.05). Intriguingly, no significant disparities were observed between the acupuncture and rehabilitation groups concerning pain and JOA scores at the 2week follow-up (p>0.05); however, 3 months post-treatment, the acupuncture group significantly outperformed the rehabilitation group in both pain and JOA scores (p<0.05).This study demonstrates that acupuncture treatment is significantly more effective than traditional rehabilitation therapy in improving paraspinal muscle function, reducing muscle fat infiltration, and alleviating lumbar and leg pain in patients with lumbar disc herniation (LDH). Specifically, acupuncture significantly increases the cross-sectional areas (Sm, Se, Sp) of the paraspinal muscles and reduces muscle fat infiltration, showing superior long-term results in pain relief and functional improvement. Future research should explore the long-term effects of acupuncture on the function of paraspinal muscles, assess potential in preventing the recurrence of LDH, and delve deeper into how acupuncture affects paraspinal muscles at the molecular level, to better understand its therapeutic mechanisms and enhance its clinical application.